The Relationship Between Religious Attitude and Breastfeeding Attitude: A Cross-Sectional Study from Türkiye - Çelik, Melike Yavaş; Tunçkaşık, Cuma (UI Scholars Hub, 2025)
Background: This study aimed to evaluate the relationship between religious attitudes and breastfeeding attitudes and the effect of this relationship on breastfeeding practices. Methods: This study was conducted with 203 mothers with babies aged 0–24 months. Simple random sampling was used in sample selection. The Religious Attitude Scale and Breastfeeding Attitudes of the Evaluation Scale were used in data collection. Results: A significant relationship was found between religious attitudes and breastfeeding attitudes. Additionally, mothers' negative breastfeeding attitudes and positive breastfeeding attitudes were found to be close to each other. The time it took for mothers to start breastfeeding their babies, the time they thought about breastfeeding their babies, the time it took to start their babies on supplementary food, and whether they fed their babies exclusively with breast milk were not found at the desired levels. Conclusions: As a result, religious attitudes and breastfeeding attitudes are related. This relationship can be used to initiate and maintain breastfeeding.